Diagnostic utility of T2*-weighted GRE in migraine with aura attack. The cortical veins sign. (July 2022) - Hirtz, Chloe; Adam, Gilles; Raposo, Nicolas; Fabre, Nelly; Ducros, Anne; Calviere, Lionel; Rousseau, Vanessa; Albucher, Jean François; Olivot, Jean-Marc; Bonneville, Fabrice; Viguier, Alain
Objective: To evaluate the frequency, distribution, and clinical associations of the dilated appearance of cerebral cortical veins, termed cortical veins sign on T2*-weighted gradient recalled-echo (T2*-GRE) in the acute setting of migraine with aura attack in adult patients. Methods: We conducted a retrospective analysis of 60 consecutive patients admitted for acute neurological symptoms with a final diagnosis of migraine with aura (42%) or probable migraine with aura (58%) who underwent emergency brain magnetic resonance imaging and 60 non-migrainous control adults. The cortical veins sign was defined as a marked hypo-intensity and/or an apparent increased diameter of at least one cortical vein. We examined the prevalence, the spatial distribution, and the associations of cortical veins sign with clinical characteristics of migraine with aura. Results: We detected the cortical veins sign in 25 patients (42%) with migraine with aura, compared to none in the control group ( p  < 0.0001). The spatial distribution of cortical veins sign was characterised by the predominantly bilateral and posterior location. Presence of cortical veins sign was associated with increased severity of aura ( p  = 0.05), and shorter delay to MRI ( p  = 0.02). Conclusion: In the setting of acute neurological symptoms, the presence of cortical veins sign is frequent in patients with migraine with aura and can be detected with good reliability. This imaging marker may help clinicians identify underlying migraine with aura.